A utiliza????o da mem??ria pelo marketing de clubes de futebol - Granja, Alex Lopes (2015)
Memory is a strategic important asset and has been used gradually and indirectly in the marketing of football clubs. For these roles it plays and the present and future potential of the memory usage of football clubs is that the objective of this study is to identify how the memory can be used in the marketing of football clubs. The theoretical references were presented the concepts of memory, collective memory and organizational memory, and was used to concepts of invention of tradition, organizational identity and nostalgia to understand how memory can be used in football clubs by marketing departments. We present also the consideration of the post-modern marketing and the retro marketing that are theories in marketing that essentially use memory. The methodology was qualitative exploratory with literature and in-depth interviews with consumers of the four clubs most twisted of S??o Paulo. To analyze the data we used the technique of content analysis. The results of this study enable football clubs to target their marketing activities that are supported in aspects of the past for the development of products, goods and services that meet adequately the concerns of its consumers and serving to identify what the past and how the past should be exalted in the actions that are anchored in the past of football clubs.